The Microbiome in Cystic Fibrosis - Huang, Yvonne J; LiPuma, John J (Clinics in chest medicine, 2016)
Observations from studies during the last decade have changed the conventional view of cystic fibrosis (CF) microbiology, which has traditionally focused on a limited suite of opportunistic bacterial pathogens. It is now appreciated that CF airways typically harbor complex microbial communities, and that changes in the structure and activity of these communities have a bearing on patient clinical condition and lung disease progression. Recent studies of gut microbiota also suggest that disordered bacterial ecology of the CF gastrointestinal tract is associated with pulmonary outcomes. These new insights may alter future clinical management of CF.